Stochastic modeling for the COMET-assay - Anne-Laure Boulesteix; Volker Hösel; Volkmar Liebscher (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
We present a stochastic model for single cell gel electrophoresis (COMET-assay) data. Essential is the use of point process structures, renewal theory and reduction to intensity histograms for further data analysis.
urn:nbn:de:bvb:19-epub-1714-1
Keywords: 519